“The First Swallow”: Avian Metaphors in Nikita Khrushchev’s Political Discourse - Carter , Elena V. (Poznańskie Studia Slawistyczne, 2021)
Birds are a rich source for metaphors in paremias that are known to be a significant rhetorical force in various modes of communication. This article deals with the repertoire of ornithological proverbial texts utilized in the Soviet leader’s public speeches and memoirs, as well as in their English translations. The metaphor human is bird, in which there are various grounds of comparison, is explored. The peculiarities of using avian metaphors in the context of the original and the ways of their translation into English are scrutinized as well. The analysis of the material shows that the main features, shared by the Target (human) and the Source (bird species), are grounded on physiological characteristics and behavioral traits, having a negative slant. The equivalent and literal translations are applied as the main methods of rendition. Of particular interest are the metaphorical “animalistic metamorphoses” found in translation.